Tinjauan Drainase Jalan Dr Setia Budi Kelurahan Rajawali Kecamatan Jambi Timur - RM Faisal; Azwarman Azwarman; Susiana Susiana (Universitas Batanghari Jambi, 2022)
Rajawali Village is one of the villages in East Jambi District which has problems with the drainage system. This is due to frequent flooding during the rainy season. The capacity of the canal is not able to accommodate rainwater, causing flooding which disrupts community activities and can cause various kinds of diseases. The purpose of this study was to analyze the performance of the drainage system and improve the drainage system in Rajawali Village, Jambi Timur District so that existing problems can be resolved. Based on the results of the analysis that has been carried out from rainfall data for a 10-year period (2010-2019), the rainfall for three minimum methods with a duration of 60 minutes is 121,259 mm/hour from the Sherman equation formula. Based on the calculations and the existing conditions in the field, the results of the existing discharge (QE) of 4.129 m3/second are smaller than the design discharge (QR) of 4.323 m3/second. So it is necessary to design a safer channel design.